Digital Marketing as a Tourism Village Marketing Strategy in East Java’s Horseshoe Region - Nurmadewi, Dita; Yuniati, Sri; Firdaus, Muhammad Vallen; Rachman, Izmil Musyaffa (Jurnal Sistem Informasi Bisnis, 2024)
If supported by digital marketing, tourism villages can be a major economic driver in rural communities. Because through digital marketing, the tourism industry is able to expand its market and attract more tourists. This study intends to map the need for information technology for digital marketing as a strategy to enhance the marketing of tourism villages. This study employs a qualitative case study methodology. Tourism villages of Kemiren in Banyuwangi Regency, Lombok Kulon in Bondowoso Regency, and Kampung Blekok in Situbondo Regency served as research sites. Observation, interviews, and documentation techniques were utilized to collect research data. The data analysis employed qualitative descriptive analysis. According to the findings of the survey, the marketing of tourist villages in the Horseshoe region has been conducted using information technology. However, the use of digital marketing through websites and social media is still limited. Therefore, digital marketing must be supported in accordance with the requirements of the tourist village and the segmentation of the target market. This research's information technology requirements mapping methodology for digital marketing can be utilized to support the marketing of tourist villages in East Java’s Horseshoe region.